Legacies from the Past and Transitions to a "Healed" Future in Brazilian Spiritist Therapy - Greenfield, Sidney M. (Anthropologica, 2022)
This paper describes a ritual healing session at a Spiritist centre in Rio de Janeiro, Brazil, where patients are treated for physical and emotional symptoms brought on by events in their previous lives. Mediums re-enact the incidents that are believed to be the cause of the present-day symptoms. Religious leaders then indoctrinate, during a ritual debate, the spirit or spirits (of parties offended or injured by the patient in the previous lifetime) responsible for causing the symptoms. When these spirits are induced to repent, the patient emerges from the session cured. Following the lead of Csordas (1983), the ritual, and the healing it provides, is analyzed in terms of the patient being moved, first rhetorically and then socially to a new state. The healing is seen as part of a process of religious conversion. The van Gennep (1960 [1908]) and Turner (1967, 1969) transition model is introduced to show the patient being separated during the healing ritual from his/her previous secular (non-Spiritist state) and then moved, first into a liminal state, and then into the new state as a believer and participant in the Spiritist religious community.